The importance of SARS-CoV-2 testing in pediatric population - Rodica Demenciuc; Lorena Elena Melit; Tudor Fleseriu; Cristina Oana Marginean (Amaltea Medical Publishing House, 2022)
Pediatric population associates multiple peculiarities in terms of SARS-CoV-2 regarding the differences of symptoms in comparison to adults, but also the higher incidence of asymptomatic cases. The aim of these case reports is to underline the importance of SARS-CoV-2 testing in pediatric patients. The first case describes the case of a 2-year and nine-month-old child admitted to the Pediatrics Clinic I Targu Mures for involuntary ingestion of toxic substance. The clinical exam pointed out a mild hyperemia of pharynx and small lymph nodes under the mandibula, on the side area of the neck and above the clavicula; and the laboratory tests pointed out leukocytosis, thrombocytosis and one of the liver transaminases above the normal limit. In spite of the presentation concerns, the patient was tested for SARS-CoV-2 infection, with positive result. The evolution was favorable during the admission. The second case describes a 3-year and 8-month-old male patient brought in the emergency department with the suspicion of foreign body aspiration, but the bronchoscopy revealed only purulent secretion in the trachea and bronchia. The RTPCR test for SARS-CoV-2 infection was negative on the admission day, but due to the slowly favorable evolution, the patient was retested on the 5th day of admission, with positive result. The testing of pediatric patients independently of the symptoms and the clinical setting might carry a higher importance in limiting the viral transmission.